Akims of Villages of the Republic of Kazakhstan - R. A. Yesbergen; G. N. Asrepov (Экономика: стратегия и практика)
The purpose is to study the mechanisms of improving the managerial efficiency of rural akims in Kazakhstan in the example of the Aktobe region. The ongoing reforms on the introduction of the institute of elections of rural akims, the decentralization of powers and the expansion of the competence of rural akims, and the introduction of independent rural budgets will strengthen the lower level of the executive branch of government. The effectiveness of the activity of akims is determined by the characteristics of the success of the professional activity of civil servants in terms of the degree of achievement of the planned result and the desired social effect, as well as the ratio of the results achieved with the resources spent on its implementation. The methods of observation, surveys, focus groups, analysis, systematization and generalization were used. In determining the effectiveness of the activities of akims by teaching methods - facilitation and brainstorming, a number of problems and ways to solve them have been identified. Materials on akims in the Department of Economy and Budget Planning and the Department of the Agency of Kazakhstan for Civil Service Affairs were also received. As the results of the study, the problematic issues identified during the training courses, seminars of rural akims of the Aktobe regional branch, and solutions identified by various active teaching methods are presented. Рossible solutions to the problematic issues identified during the survey and training are proposed. Research will be reflected in the scientific works of the doctoral student.